2003
DOI: 10.1007/s00125-003-1220-7
|View full text |Cite
|
Sign up to set email alerts
|

Processed meat intake and incidence of Type 2 diabetes in younger and middle-aged women

Abstract: Aim/hypothesis. The aim of this study was to investigate the association between processed and other meat intake and incidence of Type 2 diabetes in a large cohort of women. Methods. Incident cases of Type 2 diabetes were identified during 8 years of follow-up in a prospective cohort study of 91246 U.S. women aged 26 to 46 years and being free of diabetes and other major chronic diseases at baseline in 1991. Results. We identified 741 incident cases of confirmed Type 2 diabetes during 716276 person-years of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
162
2
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(177 citation statements)
references
References 52 publications
12
162
2
1
Order By: Relevance
“…After salty snacks people often drink sweet soft drinks, which may increase the level of postprandial glucose and may also lead to obesity and imbalanced nutrient intakes due to a reduced intake of healthier foods. The data from the Health Professionals' Follow-up Study [41] and the Nurses' Health Study [42] also found that a diet high in processed meats could increase the risk for developing type 2 diabetes. A diet with a high intake of salt from processed meats may be one potential explanation of above association.…”
Section: Discussionmentioning
confidence: 97%
“…After salty snacks people often drink sweet soft drinks, which may increase the level of postprandial glucose and may also lead to obesity and imbalanced nutrient intakes due to a reduced intake of healthier foods. The data from the Health Professionals' Follow-up Study [41] and the Nurses' Health Study [42] also found that a diet high in processed meats could increase the risk for developing type 2 diabetes. A diet with a high intake of salt from processed meats may be one potential explanation of above association.…”
Section: Discussionmentioning
confidence: 97%
“…In previous epidemiological studies, meat intake, especially processed meat, has been associated with increased risk of diabetes (Snowdon & Phillips, 1985;Colditz et al, 1992;van Dam et al, 2002b;Schulze et al, 2003). It has been hypothesized that the association is mediated by the betacell toxic effect of nitrosoamines or by saturated fat, or advanced glycation end-products (Peppa et al, 2002;van Dam et al, 2002b).…”
Section: Discussionmentioning
confidence: 99%
“…The relation between processed meat consumption and the development of diabetes has been addressed in a number of studies (Snowdon & Phillips, 1985;Colditz et al, 1992;van Dam et al, 2002b;Schulze et al, 2003). The alleged mediators include saturated fat, cholesterol, nitrites, and advanced glycation end-products (Peppa et al, 2002;van Dam et al, 2002b;Schulze et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meat intake was associated with: an increased prevalence of diabetes in men and women; and an increased diabetes-associated mortality in men, but not in women. Several subsequent publications have reported an increased risk of diabetes or type 2 diabetes with a high intake of processed meat [17][18][19][20][21][22][23], red meat [17-19, 22, 24, 25] and total meat [15,17,23], but the results have not been consistent [20,21,26,27]. To clarify this association we conducted a systematic review and meta-analysis of cohort studies of meat intake and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%